The ‘process of doing’ in everyday occupations – a challenge for young adults with cerebral palsy - L. Bergqvist; A. M. Öhrvall; M. Peny-Dahlstrand (Scandinavian Journal of Occupational Therapy)
Background: There is a lack of knowledge about how persons with cerebral palsy (CP) perceive their ‘process of doing’ while performing everyday occupations. As described in the Model of the Process of Doing (MPoD), performing an occupation is a complex process consisting of six phases (generate idea, plan, initiate, enact, adjust, end) and time management.Aim: To collect the experiences of young adults with CP, classified at Manual Ability Classification System (MACS) level I or II, regarding how they perceive challenges in their occupational performance in relation to the different phases of the ‘process of doing’.Method: Semi-structured interviews were performed with ten participants with CP aged 19–30 years, MACS level I or II. The interview material was related to the MPoD phases using directed content analysis.Results: The participants’ descriptions of how they perceived their personal ‘process of doing’ showed problems in all MPoD phases. All participants experienced difficulties in one or more phases, but none had difficulties in all phases. Difficulties were more frequent in some phases than in others.Conclusion/Significance: To understand the complexity of doing everyday occupations in young adults with CP, there is a need to address all phases of the ‘process of doing’.